Prediction On Difference In Micro, Small Medium Enterprises-Revenue After Getting Vacum Frying And Spinner Assistance - Asep Awaludin Prihanto; Rahmi Nurdiani; Yoga Dwi Jatmiko; Hidayatun Muyasyaroh (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2020)
Doktor Mengabdi is a community service program at Universitas Brawijaya that is carried out to improve the welfare of the community. One of the efforts to help the community in completing its packaging is by providing assistance in the form of business equipment. The purpose of this study is to investigate the difference in income of Small medium enterprises, Lele Sehat (IGF) which has been provided with the help of vacuum frying and spinners machines. Data retrieval was done through interviews and live observations. The data were tested for its normality and further analyzed using a paired t-test. The results showed that there was a difference in income of small-medium enterprises difference between before and after getting tool assistance. Prior income was IDR 3,007,000. It was increased to IDR. 4,097,000. This indicates that providing tools to small-medium enterprises will increase income and indirectly improve their welfare.